Rice variety Sahel 108 proves well adapted to climate change and is adopted on more than 70% of of the total rice area in Senegal - CGIAR Research Program on Rice (2021)
Sahel 108, which was released by AfricaRice in Senegal in 1994, still accounted for more than 70 % of the total rice area in 2019 because it is high-yielding and short duration allowing double cropping under climate change conditions (increasing cold stress). Recent higher re-adoption of Sahel 108 in the wet season is related to intensification in Senegal that started in 2009. Rice double cropping requires short duration varieties to avoid cold stress at the end of the wet season.